Testing of Textile Materials: Laboratory Work - Kreže, Tatjana (2019)
This Laboratory work instructions have been written for Erasmus students at the University of Maribor as educational material for carrying out laboratory analysis in the field of textile materials testing. The field of textile materials characterization is very extensive, from the identification of the structural characteristics of fibres, the physicochemical properties of fibres, the mechanical, thermal, electrical properties of fibres, etc. This laboratory work instructions are limited to the part of determining the physical properties of textile materials such as: determination of dimensional characteristics, mechanical properties, structural characteristics, and determination of application properties of different textile materials, described in the following chapters: Testing of fibres, Testing of yarns and Testing of fabrics. It is extremely important to support the laboratory work performance in conjunction with a thorough study of an up-to-date copy of the relevant standard. The actuals standards contain a wealth of detail which is not possible to cover in the instructions of this nature and furthermore national and international standards (SIST, ISO, EN…) are constantly being updated.
Keywords: textile materials testing methods; fibres; yarn; fabric; statistical terms